2004
DOI: 10.1097/00005537-200409000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Voice Handicap Index‐10

Abstract: The VHI-10 is a powerful representation of the VHI that takes less time for the patient to complete without loss of validity. Thus, the VHI-10 can replace the VHI as an instrument to quantify patients' perception of their voice handicap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
731
2
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,062 publications
(812 citation statements)
references
References 14 publications
17
731
2
22
Order By: Relevance
“…Internal consistency proved to be good, as was test-retest stability. Regarding identiWcation of voice-impaired patients, several authors used controls (subjects from the normal population without voice problems) in their randomised controlled studies on VHI change and reported mean "normal" values varying from 2.3 to 10.5 points but neither of them made a reliable eVort to deWne a cut-oV point [4,5,11,12,13]. The present study revealed a cut-oV point of 15 to identify patients with voice problems in daily life.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Internal consistency proved to be good, as was test-retest stability. Regarding identiWcation of voice-impaired patients, several authors used controls (subjects from the normal population without voice problems) in their randomised controlled studies on VHI change and reported mean "normal" values varying from 2.3 to 10.5 points but neither of them made a reliable eVort to deWne a cut-oV point [4,5,11,12,13]. The present study revealed a cut-oV point of 15 to identify patients with voice problems in daily life.…”
Section: Discussionmentioning
confidence: 59%
“…On the contrary, Speyer [18] reported a non-signiWcant median improvement of 6 points after voice therapy in patients with a diversity of chronic benign voice disorders. Other studies on the eVect of several medical treatment modalities for diVerent benign voice disorders show a mean VHI improvement ranging from 13 to 46 points [2,13,26]. All these studies on the eYcacy of voice intervention on various voice patient groups reveal that a statistical diVerence score is at least 12 points.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These 11 questions aimed to investigate the etiology of the olfactory dysfunction and related situations, and the next 11 questions aimed to create an understanding of the effects of olfactory dysfunction on the life-qualities of the volunteers (Table 1). These 11 questions were prepared in keeping with surveys on life-quality evaluation [4,11,12]. The answers to these questions were ''always, almost always, sometimes, almost never, and never''.…”
Section: Methodsmentioning
confidence: 99%
“…The patients were asked to complete the VHI-10 survey about their voice complaints [1,10,16]. This index includes 10 items assessing the impact of voice disorders on daily life.…”
Section: Subjective Voice Analysismentioning
confidence: 99%